THU0565 The Effects of Radial Shock Wave Therapy and Low Level Laser Therapy in the Treatment of Chronic Plantar Fasciitis: A Randomized Controlled Trial. (10th June 2014) - Suleymanoglu, T.; Esmaeilzadeh, S.; Sen, E.I.; Diracoglu, D.; Yaliman, A.; Eskiyurt, N.
Abstract : Objectives: The aim of this prospective, randomized controlled 3-month interventional trial was to investigate the effects of Radial Shock Wave Therapy (RSWT) and Low Level Laser Therapy (LLLT) on foot pain and plantar fascia thickness in patients with chronic plantar fasciitis. Methods: Ninety (82 female, 8 male) eligible patients with chronic plantar fasciitis who had no response to the conservative treatment methods for at least 6 months were included in the study and allocated to three groups, RSWT, LLLT and control groups. The RSWT program consisted of three sessions of the RSWT once a week. The LLLT program consisted of 12 sessions of the LLLT, three times a week for 4 weeks. All patients received instruction for home stretching exercises for three months. Foot pain was evaluated by the Visual Analogue Scale (VAS) and Foot Function Index (FFI) pain subscale. The thickness of plantar fascia was measured by ultrasound. All assessments were performed at baseline, immediately and three months after treatment. Statistical tests were conducted at the 0.05 significance level for all outcome measures. Results: Eighty-one patients (150 feet) completed the study. The mean age of the patients was 48.8±8.3 years (range 31-70). The pain intensity (VAS) was decreased significantly in RSWT group only at the 3-month assessments (0<0.001) compared with the LLLT and control groups. Moreover, there was a significant reduction in the foot pain assessed by the FFI pain subscale in the RSWT compared with the controls at the 3-month assessment (0<0.001). There was a significant decrease in the plantar fascia thickness in all three groups, but, these reductions were more significant in the RSWT group at immediately after treatment (p<0.01) and 3-month assessments (0<0.001). Conclusions: These data suggest that the RSWT is effective on reducing pain and both the RSWT and LLLT can be effective in reducing the plantar thickness in patients with chronic plantar fasciitis specially at three months after treatment. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3359